A probable case of West Nile virus transfusion transmission. Issue 3 (5th February 2017) - Groves, Jamel A.; Shafi, Hedyeh; Nomura, Jim H.; Herron, Ross M.; Baez, Devin; Dodd, Roger Y.; Stramer, Susan L.
Abstract : BACKGROUND: Transfusion‐transmitted West Nile virus (WNV) infection is infrequent as a result of minipool (MP) and individual‐donation (ID) nucleic acid testing (NAT) of blood donations. ID‐NAT is triggered on the basis of local WNV activity identified by MP‐NAT. STUDY DESIGN AND METHODS: A 78‐year‐old male patient who was treated for cardiac disease received 14 blood components from 30 donors in August 2016. He was discharged 7 days after aortic valve replacement and coronary bypass surgery, but was re‐admitted on Day 12 with symptoms of viral infection, and eventually was diagnosed with aseptic meningitis. The patent died on Day 51. RESULTS: The patient was positive for WNV‐immunoglobulin M (IgM) antibodies in his cerebrospinal fluid on Day 14 and was positive for WNV‐IgM (on Days 14 and 16) and WNV‐IgG antibodies (on Day 16) in his serum. All associated donations were nonreactive by MP‐NAT or ID‐NAT. However, one MP‐NAT was noted to have an elevated (but negative) signal‐to‐cutoff ratio, and one donor from that MP was subsequently found positive for WNV‐IgM and IgG antibodies; the donor was diagnosed with a WNV‐like viral syndrome that had an onset 3 to 5 days postdonation. The donor's plasma was transfused 12 days before the patient's onset of WNV‐meningoencephalitis. Conversion to ID‐NAT was triggered for the region 7 days after the implicated donation, which was associated with the region's first human WNV case. CONCLUSION: Despite the possibility of mosquito‐borne transmission, this was considered to be a case of transfusion‐transmitted WNV infection from an MP‐NAT–nonreactive donation collected just before triggering conversion to ID‐NAT; a rare event recognized once in 84 million donations.